Impacts of Renewable Energy Sources Integration on Charging Electric Vehicles - Mohamed Belrzaeg; Hassnen S. Snoussi (المجلة الأفروآسيوية للبحث العلمي, 2024)
Libya has a large potential for renewable energy due to its abundant sunshine and wind resources. Some renewable energy sources that Libya can harness are (solar, wind, and geothermal energy). The advanced growth in the transportation sector for using Electric Vehicles (EVs) made it popular among people to use hybrid electric vehicles instead of conventional cars. However, the transportation system become complex due to used components such as the integration of Renewable Energy Sources (RESs) into the grid for charging/discharging EVs, that is led to many challenges. The challenges of splitting the power between the thermal and electrical subsystems can be overcome by a supervisor’s control method known as Energy Management Strategies (EMS), which results in the maximization of fuel economy and minimizing pollution. The acquired result is discussed in the result and discussion section. The RESs are capable of running systems with the integration of EVs.